Effects of Carboxylic Acids on Friction and Wear Reducing Properties for Alkylmethylimidazolium Derived Ionic liquids - Hideto Kamimura (Japanese Society of Tribologists, 2006)
Lubricant additive technology to improve lubricant performances is an important issue for ionic liquids to be applied practically. Effects of carboxylic acids with different carbon chain length in ionic liquid on tribological properties were examined. Solubility of carboxylic acids was dependent on the chain length of carboxylic acids and imidazolium cations. The carboxylic acids reduced friction and wear in comparison with additive free one. It was found that friction reducing properties of carboxylic acid depended on their chain length. Interestingly, additive response of ionic liquids was found to be superior to those for conventional ester oil as base oil. Surface images obtained by an optical microscope clearly show that the additive depressed chemical wear by ionic liquids especially at low load. Surface analysis with EPMA supported films of carboxylic acids as a cause of improvement of friction property. Therefore, the mechanism of carboxylic acids was considered to provide adsorbed film which accompanied with low friction and anti-wear properties.